2018
DOI: 10.1109/twc.2018.2868710
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Mobile-Edge Computation Offloading: Energy-Efficient Resource Management

Abstract: Mobile-edge computation offloading (MECO) is an emerging technology for enhancing mobiles' computation capabilities and prolonging their battery lifetime, by offloading intensive computation from mobiles to nearby servers such as base stations. In this paper, we study the energy-efficient resourcemanagement policy for the asynchronous MECO system, where the mobiles have heterogeneous inputdata arrival time instants and computation deadlines. First, we consider the general case with arbitrary arrival-deadline o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(48 citation statements)
references
References 44 publications
(84 reference statements)
0
48
0
Order By: Relevance
“…How to improve EE of mobile devices in MEC systems subject to the delay constraint has been widely studied in existing literature [7,8,[12][13][14]. To study the tradeoff between EE and latency, a weighted sum of energy consumption and latency was minimized in a single-AP scenario [7].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…How to improve EE of mobile devices in MEC systems subject to the delay constraint has been widely studied in existing literature [7,8,[12][13][14]. To study the tradeoff between EE and latency, a weighted sum of energy consumption and latency was minimized in a single-AP scenario [7].…”
Section: Related Workmentioning
confidence: 99%
“…With this scheme, there is no exploration and the output of the DNN will be used as the user association scheme. Some similar studies focused on offloading and resource allocation with a single AP [8,18]. The implicit assumption on the user association is that the users are served by the nearest AP or the AP with the highest large-scale channel gain.…”
Section: DL Algorithm For User Associationmentioning
confidence: 99%
See 1 more Smart Citation
“…In [15], a user scheduling scheme was proposed to MEC in order to achieve a balanced tradeoff between the latency and reliability for task offloading. In [16], a more challenging multi-user MEC scenario was considered, where the users offload their tasks to the MEC server in an asynchronous manner. Initial studies in [17] and [18] have already demonstrated the benefit for the application of NOMA to MEC, by developing various optimization frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [14] presented an energy-efficient computation offloading scheme that incurs minimal energy consumption under latency constraints by optimizing the offloading policy and radio resource allocation for MEC in 5G heterogeneous networks with multiaccess characteristics. You et al [15], based on insight into the input data arrival time instants and computation deadlines, studied an energy-efficient resource management policy for MECO systems and formulated an optimization strategy that minimizes the total mobile-energy consumption. Unfortunately, these works are mainly interested in reducing the energy consumption without attempting to reduce the completion time of computation tasks.…”
Section: Introductionmentioning
confidence: 99%